Comparisons Between Serum Levels of Hepcidin and Leptin in Male College-Level Endurance Runners and Sprinters - Nirengi, Shinsuke; Taniguchi, Hirokazu; Ishibashi, Aya; Fujibayashi, Mami; Akiyama, Nao; Kotani, Kazuhiko; Ishihara, Kengo; Sakane, Naoki (Frontiers in Nutrition, 2021)
Background: Hepcidin-25 is a 25 amino acid hepatokine and a key regulator of iron metabolism related to iron deficiency anemia. Recent studies have suggested that an elevated hepcidin level is correlated with low energy availability. Leptin is an appetite-suppressing adipokine and has been reported to stimulate hepcidin production in animals and cultured cells. While leptin is modulated by exercise, it is known that endurance runners and sprinters practice different types of exercise. This study investigated and compared the relationships between hepcidin and leptin levels, iron status, and body fat to understand better the risk of iron deficiency anemia in endurance runners and sprinters. Methods: Thirty-six male college track and field athletes (15 endurance runners and 21 sprinters) were recruited for this study. Dietary intake, body composition, and blood levels of ferritin, hepcidin-25, leptin, and adiponectin were measured. Correlations between hepcidin levels and ferritin, body fat, leptin, and adiponectin were evaluated using Pearson’s correlation coefficient for each group. Results: The endurance runners had lower hepcidin levels and higher leptin and adiponectin levels compared with sprinters. Ferritin was positively correlated with hepcidin-25 levels in both the endurance and sprinter groups. A positive correlation was observed between hepcidin-25 and body fat or leptin levels only in sprinters. Conclusion: This is the first study investigating the relationship between blood levels of hepcidin and leptin in athletes. The positive correlation between hepcidin-25 and leptin in sprinters but not endurance runners.